2017
DOI: 10.18632/oncotarget.22170
|View full text |Cite
|
Sign up to set email alerts
|

Role of tandospirone, a 5-HT1A receptor partial agonist, in the treatment of central nervous system disorders and the underlying mechanisms

Abstract: 5-hydroxytryptamine (5-HT, serotonin) is an important neurotransmitter in the modulation of the cognitive, behavioral and psychological functions in animals and humans. Among the fourteen subtypes of 5-HT receptor, 5-HT1A receptor has been extensively studied. Tandospirone, an azapirone derivative with strong and selective agonist effect on 5-HT1A receptor, has been used for the treatment of anxiety disorders especially generalized anxiety disorder for decades. Recently, tandospirone showed the efficacy in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 135 publications
(142 reference statements)
0
18
0
Order By: Relevance
“…Development of partial agonist drugs is therefore of interest whenever overstimulation of a GPCR needs to be prevented by tuning the receptor response (Hauser et al, 2017). GPCR partial agonists currently used in the clinic or investigated for their therapeutic potential include drugs targeting opioid receptors (Browne et al, 2020;Chan et al, 2017;Fujimura et al, 2017;Khroyan et al, 2017;Schmid et al, 2017), adrenergic receptors (Calverley et al, 2007), dopamine receptors (Frank et al, 2017;Tarland et al, 2018), and serotonin receptors (Chen et al, 2018;Huang et al, 2017;Yoshinaga et al, 2018;Zheng et al, 2017). Partial agonists are also under consideration as potential treatments for obesity (Wargent et al, 2013) and heart failure (Greene et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Development of partial agonist drugs is therefore of interest whenever overstimulation of a GPCR needs to be prevented by tuning the receptor response (Hauser et al, 2017). GPCR partial agonists currently used in the clinic or investigated for their therapeutic potential include drugs targeting opioid receptors (Browne et al, 2020;Chan et al, 2017;Fujimura et al, 2017;Khroyan et al, 2017;Schmid et al, 2017), adrenergic receptors (Calverley et al, 2007), dopamine receptors (Frank et al, 2017;Tarland et al, 2018), and serotonin receptors (Chen et al, 2018;Huang et al, 2017;Yoshinaga et al, 2018;Zheng et al, 2017). Partial agonists are also under consideration as potential treatments for obesity (Wargent et al, 2013) and heart failure (Greene et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies reported that tandospirone regulates cognitive function in dizocilpine-treated rats (Bubenikova-Valesova et al, 2010). Tandospirone has also been found to activate presynaptic 5-HT1A receptors under certain conditions (Huang et al, 2017;Kishimoto et al, 2000;Takada et al, 1996). Therefore, it can be speculated that tandospirone has a dose-dependent effect on presynaptic/postsynaptic 5-HT1A receptors, which lead to the different effects on cognitive CIAS.…”
Section: Discussionmentioning
confidence: 98%
“…Dizocilpine, quetiapine, WAY100635 (N-[2-[4-(2methoxyphenyl)-1-piperazinyl] ethyl]-N-(2-pyridinyl) cyclohexane carboxamide, a potent and selective antagonist of the presynaptic 5-HT1A receptor) (Sato et al, 2007) and tandospirone (a partial 5-HT1A receptor agonist, and dose-dependent activator of both pre-and postsynaptic 5-HT1A receptor) (Huang et al, 2017;Kishimoto et al, 2000;Takada et al, 1996) were all purchased from Sigma-Aldrich Corporation (St. Louis, Mo., USA) and dissolved into polyethylene glycol 400 diluted with isotonic saline. Drugs were administered intraperitoneally or by lavage administration.…”
Section: Drug Administrationmentioning
confidence: 99%
“…6 shows mechanisms related to possible therapeutic effect of 5-hydroxytryptamine receptor 1 A (HTR1A) activation. Tandospirone, a partial agonist of HTR1A, is effective in the treatment of behavioral and psychological symptoms associated with dementia 53 . The activation of HTR1A is associated with neuroprotective, anti-inflammatory and anti-oxidative effects, as well as preventing of permeability changes in blood-brain barrier 54,55 .…”
Section: Discussionmentioning
confidence: 99%